2018
DOI: 10.1159/000489636
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Organ Prolapse Repair with Mesh: Mid-Term Efficacy and Complications

Abstract: Introduction: Our aim was to assess the efficacy and complications of pelvic organ prolapse (POP) correction with transvaginal mesh (TVM). Materials and Methods: We retrospectively assessed patients who had undergone a repair of an apical (primary or recurrent) or recurrent POP using TVM in our department since 2007. Meshes used were Prolift®, Elevate®, and Surelift®. Satisfaction with surgery was assessed on a 0–10 scale. Results: A total of 83 patients were included (33 Prolift®, 36 Elevate®, 14 Surelift®), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…However, the data on quality of life, sexuality, and the complications presented here give an indication that, with the further development of implants, the surgical treatment of pelvic organ prolapse with the implantation of an alloplastic mesh has had fewer complications and has become more satisfactory for patients with regard to the postoperative quality of life, including sexuality. In the past 3 years, short-term as well as long-term data on vaginal mesh implantations have been continuously published 43 , 44 , 45 , 46 , 48 . This shows that this surgical method represents a treatment which is currently widely used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the data on quality of life, sexuality, and the complications presented here give an indication that, with the further development of implants, the surgical treatment of pelvic organ prolapse with the implantation of an alloplastic mesh has had fewer complications and has become more satisfactory for patients with regard to the postoperative quality of life, including sexuality. In the past 3 years, short-term as well as long-term data on vaginal mesh implantations have been continuously published 43 , 44 , 45 , 46 , 48 . This shows that this surgical method represents a treatment which is currently widely used.…”
Section: Discussionmentioning
confidence: 99%
“…Allerdings geben die hier präsentierten Daten zur Lebensqualität, Sexualität und den Komplikationen durchaus einen Hinweis, dass mit der Weiterentwicklung der Implantate die operative Therapie des Descensus genitalis mit Implantation eines alloplastischen Netzes komplikationsärmer und für die Patientinnen im Hinblick auf die postoperative Lebensqualität inklusive der Sexualität zufriedenstellender geworden ist. In den letzten 3 Jahren wurden kontinuierlich Daten, sowohl Kurz- als auch Langzeit, zu vaginalen Netzimplantationen veröffentlicht 43 , 44 , 45 , 46 , 48 . Dies zeigt, dass dieses operative Verfahren eine aktuell vielfach eingesetzte Therapie darstellt.…”
Section: Diskussionunclassified
“…Many studies have reported the prolapse recurrence rate of TVM surgery, which varies within 7.2-20.9% [4,[12][13][14][15][16][17][18]. To date, merely a limited number of studies that have been followed up for >5 years have reported the long-term outcomes of TVM.…”
Section: Discussionmentioning
confidence: 99%
“…For uterus- sparing prolapse repair, apart from AHSP, other abdominal procedures have been described including combined vaginal-abdominal retropubic uterine suspension, pectineal ligament uterine suspension and hysterosacropexy [22,23]. Vaginal procedures have also been described to result in satisfactory outcomes [24][25][26][27][28]. As in the case of abdominal access to prolapse repair, studies evaluating the vaginal approach with concomitant hysterectomy versus uterus preservation have shown no difference in the, overall low, rates of prolapse recurrence [26,27].…”
Section: Discussionmentioning
confidence: 99%